Goldmining in foreclosure properties - Achenbach, George (John Wiley & Sons, 2003)
The bestselling classic updated and expanded for today's booming real estate market This latest edition of George Achenbach's bestselling guide shows investors and first-time buyers how to reap the benefits of the foreclosure process. Readers get a proven system for locating and acquiring potential properties, along with valuable forms and checklists that help guide investors through every phase of the foreclosure investment cycle. The author also delineates expert techniques and strategies that enable buyers to pay off loans, save the homeowner's credit, and acquire properties at a bargain price to live in, lease, or resell. New to this edition are an Introduction featuring the latest statistics on foreclosures and the state of the economy; a chapter on bankruptcy; and extensive coverage of the homestead exemption, the "needs-based" rules, and additional recent changes in the real estate laws. George Achenbach (Laguna Hill, CA) is president of a private venture capital and income property investment company. He has started ten successful businesses, and he has built over seven thousand homes and apartments and many commercial and industrial projects.